Factors Influencing Customer Satisfaction in Woven Fabric Business Mediated by Trust Intention and Emotions - Agus Nakkok Simanjuntak; Tri Melda Mei Liana; Christnova Hasugian; Jenny Mirony Simanjuntak; Grace Sitanggang (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study aims to analyze the effect of total quality management and digital marketing on customer satisfaction with trust intention and emotional response as mediating variables in small woven fabric businesses in an area. This quantitative study used 150 respondents and was processed with SmartPLS 4.0. The results show that digital marketing has a significant effect on customer satisfaction (p = 0.000) and emotional response (p = 0.001), but not significant on trust intention (p = 0.085). Emotional response and total quality management have a significant effect on customer satisfaction (p = 0.000). Quality management also has a significant effect on emotional response (p = 0.045) and trust intention (p = 0.000). Trust intention has a significant effect on emotional response (p = 0.000). In terms of mediation, digital marketing has a significant effect on customer satisfaction through emotional response (p = 0.006), while total quality management has a significant effect through trust intention and emotional response (p = 0.01). These results are expected to be a reference in improving service quality and policy making.